ANALISIS TINDAKAN ILOKUSI DALAM FILM “SING”. - Sukmawati, Darumas Bunga (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
Illocutionary act is one of the sub-fields studied in speech acts. Illocutionary acts can be studied in movies, one of which can be through the